Construct Validity and Reliability of the SARA Gait and Posture Sub-scale in Early Onset Ataxia - Lawerman, Tjitske F.; Brandsma, Rick; Verbeek, Renate J.; van der Hoeven, Johannes H.; Lunsing, Roelineke J.; Kremer, Hubertus P. H.; Sival, Deborah A. (Frontiers in Human Neuroscience, 2017)
Aim: In children, gait and posture assessment provides a crucial marker for the early characterization, surveillance and treatment evaluation of Early Onset Ataxia (EOA). For reliable data entry of studies targeting at gait and posture improvement, uniform quantitative biomarkers are necessary. Until now, the pediatric test construct of gait and posture scores of the Scale for Assessment and Rating of Ataxia sub-scale (SARA) is still unclear. In the present study, we aimed to validate the construct validity and reliability of the pediatric (SARAGAIT/POSTURE) sub-scale. Methods: We included 28 EOA patients (15.5 (6-34) years; median (range)). For inter-observer reliability, we determined the ICC on EOA SARAGAIT/POSTURE sub-scores by three independent pediatric neurologists. For convergent validity, we associated SARAGAIT/POSTURE sub-scores with: 1. Ataxic gait Severity Measurement by Klockgether (ASMK; dynamic balance), 2. Pediatric Balance Scale (PBS; static balance), 3. Gross Motor Function Classification Scale -extended and revised version (GMFCS-ER), 4. SARA-kinetic scores (SARAKINETIC; kinetic function of the upper and lower limbs), 5. Archimedes Spiral (AS; kinetic function of the upper limbs), and 6. total SARA scores (SARATOTAL; i.e. summed SARAGAIT/POSTURE, SARAKINETIC and SARASPEECH sub-scores). For discriminant validity, we investigated whether EOA co-morbidity factors (myopathy and myoclonus) could influence SARAGAIT/POSTURE sub-scores. Results: The inter-observer agreement (ICC) on EOA SARAGAIT/POSTURE sub-scores was high (.97). SARAGAIT/POSTURE was strongly correlated with the other ataxia and functional scales [ASMK (rs= -.819; p< .001); PBS (rs=-.943; p< .001); GMFCS-ER (rs= -.862; p< .001); SARAKINETIC (rs= .726; p<.001); AS (rs .609; p= .002) and SARATOTAL (rs= .935; p<.001)]. Comorbid myopathy influenced SARAGAIT/POSTURE scores by concurrent muscle weakness, whereas comorbid myoclonus predominantly influenced SARAKINETIC scores. Conclusion: In young EOA patients, separate SARAGAIT/POSTURE parameters reveal a good inter-observer agreement and convergent validity, implicating the reliability of the scale. In perspective of incomplete discriminant validity, it is advisable to interpret SARAGAIT/POSTURE scores for comorbid muscle weakness.